PENGARUH PENGELUARAN PEMERINTAH SEKTOR PENDIDIKAN, KESEHATAN DAN TPAK TERHADAP IPM DI INDONESIA - Ulfa Maulina; Devi Andriyani (LPPM Universitas Malikussaleh – Indonesia, 2020)
This study aims to determine the effect of government spending of education sector, health and level of labor force participation on human development index in Indonesia. This study used time series data from 2005 to 2019. The method of data analysis uses multiple regression analysis. The results of partially show that government expenditure of education sector has a negative and significant effect on human development index in Indonesia, government spending of health sector has a positif and significant effect on human development index in Indonesia, and the level of labor participation has a positive but insignificant effect on human development index in Indonesia. Simultaneously, government spending of education sector, health, and level of labor participation have a positive and significant effect on the human development index in Indonesia.